Hubungan antara Pre-Eklamsia pada Primi-Gravida dengan Berat Badan Lahir Rendah di RSUD Cilacap Periode Januari-Desember 2005 - Asih, Yuni; Saryono,; Kurniati, Puji (Jurusan Keperawatan FIKES UNSOED, 2006)
Indonesia is under developing country which has the highest percentages of the mother mortals in ASEAN, about 95% that is caused by obstetric complication. Preeklampsia and Eklampsia were the second main cause of the mother mortals. The account of the Preeklampsia on the period of September 2004-September 2005 were up to 77 cases. The aim of this research was to find out the relationship between the Preeklampsia a primigravida and the Low Birth Weight in Regional Public Hospita of Cilacap on the period January to December 2005. This research used cross sectional aprroach. The population were all of the Mawar room's pregnant women of the Regional Public Hospital of Cilacap on the period of January - December 2005. The data collection used the observation paper of the medical data record and register book of the Mawa room's midwife of Regional Public Hospital of Cilacap. The account of the Preeklampsia on primigravida in Regional Publik Hospital of Cilacap on the period of January-December 2005 were 52 cases (59,1%). The result of the chi square analysis showed that a relationship between the Preeklampsia on primigravida and the Low Birth Weight (p